Inxeba (The Wound): Sexual, Gender, Cultural and Religious Traumata on the African Screen. Issue 4 (2nd October 2018) - Kirby-Hirst, Mark; Karam, Beschara
Abstract: This article is divided into two distinct parts. The first part contextualises John Trengove's internationally renowned, award-winning, feature-length isiXhosa film, Inxeba . The second part of the article is an interview with Batana Vundla, conducted by Mark Kirby-Hirst (Film Theory and Visual Discourse Subject Manager at The Open Window), held in mid-2018, shortly after the High Court's decision was made public regarding the final classification of Inxeba . The interview ranges from Batana Vundla's history in the South African film and television industries, to the production processes behind the scenes of the film and concludes with a focus on the nuanced manner through which the film often broaches a wide variety of physical and psychic traumata.